A Pilot Study Evaluating Shaved Cavity Margins with Micro‐Computed Tomography: A Novel Method for Predicting Lumpectomy Margin Status Intraoperatively. Issue 5 (17th June 2013) - Tang, Rong; Coopey, Suzanne B.; Buckley, Julliette M.; Aftreth, Owen P.; Fernandez, Leopoldo J.; Brachtel, Elena F.; Michaelson, James S.; Gadd, Michele A.; Specht, Michelle C.; Koerner, Frederick C.; Smith, Barbara L.
Abstract Microscopically clear lumpectomy margins are essential in breast conservation, as involved margins increase local recurrence. Currently, 18–50% of lumpectomies have close or positive margins that require re‐excision. We assessed the ability of micro‐computed tomography (micro‐CT) to evaluate lumpectomy shaved cavity margins (SCM) intraoperatively to determine if this technology could rapidly identify margin involvement by tumor and reduce re‐excision rates. Twenty‐five SCM from six lumpectomies were evaluated with a Skyscan 1173 table top micro‐CT scanner (Skyscan, Belgium). Micro‐CT results were compared to histopathological results. We scanned three SCM at once with a 7‐minute scanning protocol, and studied a total of 25 SCM from six lumpectomies. Images of the SCM were evaluated for radiographic signs of breast cancer including clustered microcalcifications and spiculated masses. SCM were negative by micro‐CT in 19/25 (76%) and negative (≥2 mm) by histopathology in 19/25 (76%). Margin status by micro‐CT was concordant with histopathology in 23/25 (92%). Micro‐CT overestimated margin involvement in 1/25 and underestimated margin involvement in 1/25. Micro‐CT had an 83.3% positive predictive value, a 94.7% negative predictive value, 83.3% sensitivity, and 94.7% specificity for evaluation of SCM. Evaluation of SCM by micro‐CT is an accurate and promising method of intraoperative margin assessment in breast cancer patients. The scanning time required is short enough to permit real‐time feedback to the operating surgeon, allowing immediate directed re‐excision.